Time-restricted feeding improves metabolic syndrome by activating thermogenesis in brown adipose tissue and reducing inflammatory markers - Gong, Yueling; Zhang, Honghui; Feng, Jiang; Ying, Li; Ji, Mengmeng; Wei, Shiyin; Ma, Qiming (Frontiers in Immunology, 2025)
BackgroundObesity and metabolic syndrome (MetS) have become increasingly significant global health issues. Time-restricted feeding (TRF), as a novel dietary intervention, has garnered attention in recent years. However, there is limited research focusing on the effects of TRF on energy expenditure and systemic low-grade inflammation. This study aims to investigate the impact of TRF on weight management, glucose metabolism, insulin resistance, and lipid metabolism in male C57BL/6J mice, particularly in the context of metabolic disorders induced by a high-fat diet (HFD).MethodsC57BL/6J mice were divided into two groups: a normal diet (ND) group and a high-fat diet (HFD) group. The study duration was 12 weeks. Key parameters observed included body weight, glucose tolerance (via glucose tolerance tests), insulin resistance (HOMA-IR), and insulin secretion under glucose stimulation. Additionally, liver tissue was subjected to Oil Red O staining to assess lipid accumulation, and white and brown adipose tissues were stained with hematoxylin and eosin (HE) to evaluate adipocyte size. The expression of hepatic lipogenesis-related genes (Srebp-c, Chrebp, Fasn, and Acc1) and thermogenic genes in brown adipose tissue (UCP1 and PGC-1α) were also measured. Furthermore, temperature changes in the interscapular brown adipose tissue (BAT) were monitored.ResultsIn the ND group: TRF improved insulin resistance and reduced circulating levels of the pro-inflammatory cytokine IL-6, with a slight reduction in body weight.In the HFD group: TRF significantly mitigated weight gain, improved glucose tolerance and insulin resistance, and enhanced insulin secretion under glucose stimulation. Additionally, TRF reduced hepatic steatosis by downregulating the expression of lipogenesis-related genes in the liver. TRF also increased thermogenesis by upregulating the expression of thermogenic genes (UCP1 and PGC-1α) in BAT, while lowering serum levels of pro-inflammatory cytokines IL-6 and TNF-α, though IL-1β levels remained unchanged.ConclusionThis study demonstrates that TRF can activate thermogenesis in brown adipose tissue and reduce inflammation maker, leading to an improvement in hepatic steatosis and a reduction in white adipose tissue accumulation. These findings suggest that TRF may be a promising intervention for mitigating metabolic disturbances associated with obesity and metabolic syndrome. The study provides mechanistic insights into the beneficial effects of TRF, highlighting its potential in modulating lipid metabolism and exerting anti-inflammatory effects.